The Use of Youtube Videos as a Learning Media to Improve EFL Students’ Speaking Skill - Aleksius, Madar; Muer, Filomena; Siwa, Yohanis Nurak (Universitas Pahlawan Tuanku Tambusai, 2026)
Speaking skills are crucial in learning English as a Foreign Language (EFL); however, many Indonesian students face challenges in fluency, vocabulary use, grammatical accuracy, pronunciation, and coherence due to limited exposure to authentic English. This study aims to examine the effectiveness of YouTube videos as a learning medium for improving students’ speaking skills. The research employed Classroom Action Research (CAR) involving twelfth-grade students of the Interior Design major at SMK Negeri 4 Kupang. Conducted in two learning cycles, the instructional procedures involved watching English vlog videos, guided discussion of language expressions, paired speaking practice, and individual oral performance. The study utilized speaking tests consisting of a pre-test, post-test 1, and post-test 2, as well as classroom observation sheets. Students’ speaking performance was assessed based on grammar, vocabulary, pronunciation, fluency, and coherence. The findings revealed consistent improvement across all speaking aspects. Students’ scores increased from 40–78 in the pre-test to 63–84 in post-test 1 and further to 72–92 in post-test 2. Classroom observations also indicated increased student engagement, confidence, and participation during speaking activities. These findings suggest that YouTube videos effectively enhance EFL students’ speaking skills while fostering an interactive and motivating learning environment.